PROSES PENANAMAN NILAI-NILAI KETAMANSISWAAN MELALUI BUDAYA SEKOLAH DI SD TAMAN MUDA IBU PAWIYATAN YOGYAKARTA TAHUN PELAJARAN 2016/2017 - Rizki Dwi Lestari; Trisharsiwi Trisharsiwi (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to obtain a picture of the proccess planting values Ketamansiswaan trought school culture at SD Taman Muda Ibu Pawiyatan Yogyakarta. This study a qualitative research study used to examine the condition of natural object. The subjects of this study consisted of one principal, one teacher of karawitan and tembang, one teacherÂ of dance and dolanan anak, five classroom teacher and three student representing classes four and five. The data obtained are teseted its validity by increasing persistence, triangulation, andÂ using reference material. The result showed that in SD Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta.Â The proccess of planting values Ketamansiswaan trought school culture at SD Taman Muda Ibu Pawiyatan Yogyakarta are (1) proccess of planting values Ketamansiswaan trought school culture by habituation and include students in the school programs and activities and throught learning, (2) the values of Ketamansiswaan are formed kodrat alam, independence, culture, nationality, and humanity, (3) obstacles facing factors science of tecnology, material, parents, human resources, lack of time, gaps and diversity, the solution by infussing as many cultures as possible, collect HP, includding work shop activities and training Ketamansiswan, meeting with parents of students, varied learning methods, seating position, and learning tailored to the willingness and ability of students.